(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we consider a system of rational difference equations and we will prove that the unique positive equilibrium point of this system is globally asymptotically stable. We also determine the rate of convergence of a solution that converges to the equilibrium point (x; y) of this system.